(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In this article the review is created of architectures of popular data centre monitoring tools and corresponding information processing techniques are summarised. Pros and cons analysis of the monitoring tools is done and novel approach is offered by utilizing Artificial Intelligence (AI), Machine Learning (ML) and Anomaly Detection (AD) algorithms to achieve research goals and prove hypothesis that data centre level monitoring model could be built using combined AI, ML and AD techniques. Oracle performance metric data are collected to perform the information analysis from such angles the most modern enterprise monitoring tools do not provide yet.